The reform of the Italian Legislation on Childhood immunization (Epidemiology, Biostatistics, and Public Health, 2022)
Over the past few decades, giant strides have been made in the field of vaccinations, the range of vaccines available has been broadened, with a higher degree of safety and effectiveness. Paradoxically, distrust towards childhood immunization has also increased in the public opinion, a significant share of which sees not so much its advantages as the possibility of potentially serious side-effects. Vaccinations pose an issue as to the reconciliation of interests pertaining, on the one hand, to the safeguard of health, spelled out in art.13 of the Italian Constitution, and to the freedom of personal choice, protected in art.13, on the other. Therefore, the question to which the authors of this paper have sought to answer reads as follows: should immunization, and childhood immunization in particular, be deemed mandatory treatment, or is it best left up to the parents to choose? The legislation on the subject appears outdated and untimely, and the dichotomy between “mandatory vaccination” and “recommended vaccination” only adds to the sense of confusion in the public opinion. It appears necessary to improve the quality of vaccination counseling practices in childcare, but such activities need to take place within the framework of a broader strategy, centered on the fostering of a culture of prevention, backed by scientific research to the fullest extent possible. The paper’s authors point to the absolute necessity for a new, updated set of national regulations aimed at overcoming current inconsistencies and the discrepancies in guidelines set forth by each region.